2020
DOI: 10.20435/multi.v21i59.2803
|View full text |Cite
|
Sign up to set email alerts
|

Propriedades químicas de madeiras nativas comerciais

Abstract: A qualidade da madeira está relacionada com seu uso e o conjunto das propriedades químicas, físicas, anatômicas e mecânicas que lhe conferem características tecnológicas. O objetivo deste trabalho foi analisar o teor de extrativos, o teor de lignina e o pH de madeiras de florestas autóctones, visando predizer e/ou aprimorar suas utilizações. Foram quantificados os teores de extrativos solúveis em água fria e quente, NaOH 1% e etanol/tolueno, o teor de lignina e o pH. A partir do teste de médias, constataram-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
0
0
Order By: Relevance
“…It was observed that the basic and apparent density of H. courbaril and D. odorata branch wood did not differ from the stem wood values. They were also similar to the values observed in other research for stem wood of the same species [32][33][34][35][36][37][38]. For H. petraeum, these values are lower than the stem wood values, although it should be noted that they corroborate the results from the literature for stem wood of the same species [39,40].…”
Section: Physical Propertiessupporting
confidence: 91%
“…It was observed that the basic and apparent density of H. courbaril and D. odorata branch wood did not differ from the stem wood values. They were also similar to the values observed in other research for stem wood of the same species [32][33][34][35][36][37][38]. For H. petraeum, these values are lower than the stem wood values, although it should be noted that they corroborate the results from the literature for stem wood of the same species [39,40].…”
Section: Physical Propertiessupporting
confidence: 91%